Agronomic performance of new strawberry cultivars in southern Brazil - Santos, Marllon Fernando Soares dos; Fagherazzi, Antonio Felippe; Lima, Juliana Martins de; Costa, Bruna Miranda; Nerbass, Francine Regianini; Kretzschmar, Aike Anneliese; Rufato, Leo (Revista de Ciências Agroveterinárias, 2021)
The choice of cultivars to be used by strawberry farmers is essential since it could determine the success of the crop. The present study aimed to evaluate the productive and qualitative performance of strawberry genotypes grown in Vacaria, RS, Brazil. Twelve strawberry genotypes were compared, constituting the different treatments: cultivars Strawberry Festival, Oso Grande, Jonica, and Pircinque, and selections FRF PA3, FRF CE 51, FRF CE 56, FRF PIR 29, FRF PIR 54, FRF 85.04, FRF 149.18, and FRF 102.21. The seedlings were transplanted on May 13, 2014, in a semi-hydroponic cultivation system, adopting a randomized block design with four blocks and an experimental unit of ten useful plants. The variables evaluated were the number of fruits, total production per plant, productivity, commercial productivity, fresh fruit mass, commercial percentage, soluble solids, titratable acidity, soluble solids to total acidity ratio, pulp firmness, and production seasonality. The mean values ​​were subjected to an analysis of variance and multivariate analysis, and their means were compared by the Scott-Knott test at a 5% error probability. Cultivar Strawberry Festival and selection FRF 102.21 showed higher productions (1138 g plant-1 nd 1019 g plant-1, respectively) and quantities of fruits produced (85 un plant-1 and 87 un plant-1, respectively). Cultivar Jonica and selection FRF 85.4 showed higher percentages of marketable fruits. The Pircinque cultivar was prominent for sugar content, presenting a value 24% superior to the general average of the cultivars. Cultivars Strawberry Festival, Jonica, and Pircinque and selection FRF 102.21 showed the highest qualitative and quantitative gains for the region of Vacaria, RS, Brazil.